Guess what? Different source-guessing strategies for old versus new information. Issue 3 (16th March 2021) - Wulff, Liliane; Bell, Raoul; Mieth, Laura; Kuhlmann, Beatrice G.
ABSTRACT: The probability-matching account states that learned specific episodic contingencies of item types and source dominate over general schematic expectations in source guessing. However, recent evidence from Bell et al. [(2020). Source attributions for detected new items: Persistent evidence for schematic guessing. Quarterly Journal of Experimental Psychology, 73 (9), 1407–1422] suggest that this only applies to source guessing for information that is recognised as belonging to a previously encoded episode. When information was detected as being new, participants persisted in applying schematic knowledge about the sources' profession. This dissociation in source guessing for detected-old and detected-new information may have been fostered by the specific source-monitoring paradigm by Bell et al. (2020 ) in which sources were a group of individuals in a certain profession rather than fixed persons from that profession for whom episodic contingencies are more likely to persist also for new information. The aim of the present study was to test whether source guessing for detected-old versus detected-new information also dissociates in a more typical source-monitoring task, the doctor-lawyer paradigm, in which one individual doctor and one lawyer present profession-related information. Despite this change in paradigm, source guessing was based on the item-source contingency only for detected-old information, whereas schematic knowledge persisted for detected-new information. The present study thus adds evidence for persistent schema-based source guessing for new information.